A Genomotaxonomy View of the Bradyrhizobium Genus - Ormeño-Orrillo, Ernesto; Martínez-Romero, Esperanza (Frontiers in Microbiology, 2019)
Whole genome analysis of the Bradyrhizobium genus using average nucleotide identity and phylogenomics showed the genus to be essentially monophyletic with seven robust groups within this taxon that includes nitrogen-fixing nodule forming bacteria as well as free living strains. Despite the wide genetic diversity of these bacteria no indication was found to suggest that the Bradyrhizobium genus have to split in different taxa. Bradyrhizobia have larger genomes than other genera of the Bradyrhizobiaceae family, probably reflecting their metabolic diversity and different lifestyles. Few plasmids in the sequenced strains were revealed from rep gene analysis and a relatively low proportion of the genome is devoted to mobile genetic elements. Sequence diversity of recA and glnII gene metadata was used to theoretically estimate the number of existing species and to predict how many would exist. There may be many more species than those presently described with predictions of around 800 species in nature. Different arguments are presented suggesting that nodulation might have arose in the ancestral genus Bradyrhizobium.